Regulamentaç\~ao técnica, acordos comerciais e multilateralismo - Luís Fernando Tironi (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– Technical regulation plays na important role in the normative framework of multilateralism led by the WTO. This is due to its possible use as a trade barrier. The treatment of the topic of technical regulation followed the evolution of the rules of the WTO agreements, and constitutes one of the elements relevant to the context of the inquiries that have arisen about the need for adjustments to the rules of the organization. The evolution of the multilateralism was adaptive to the demands raised by the emergence of bilateral, plurilateral, regional preference agreements, seeking to remain faithful to the principles of free trade. This perspective raises the question of how technical regulation will be impacted, and conversely, how it can impact the future evolution of multilateralismo.The future of multilateralism will certainly be influenced by interests of the three mega poles of global power, U.S., China and the EU. In terms of technical regulation, other countries will make the choices or combination of choices that better suir their interests. This work intend to be a subsidy to these choices.
Keywords: F13; 330; technical regulation; commercial agremment; multilateralism